2021
DOI: 10.1007/s10822-020-00371-5
|View full text |Cite
|
Sign up to set email alerts
|

WIDOCK: a reactive docking protocol for virtual screening of covalent inhibitors

Abstract: Here we present WIDOCK, a virtual screening protocol that supports the selection of diverse electrophiles as covalent inhibitors by incorporating ligand reactivity towards cysteine residues into AutoDock4. WIDOCK applies the reactive docking method (Backus et al. in Nature 534:570–574, 2016) and extends it into a virtual screening tool by introducing facile experimental or computational parametrization and a ligand focused evaluation scheme together with a retrospective and prospective validation against vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…Fosfomycin is the unique clinically available inhibitor of MurA acting competitively against phosphoenolpyruvate. Its mode of action is related to the covalent binding to the thiol group of Cys115 residue in the active site of MurA ( Kahan et al, 1974 ; Falagas et al, 2016 ; Sutanto et al, 2020 ; Scarpino et al, 2021 ). Naturally produced by Streptomyces spp.…”
Section: Fosfomycin As Food and Drug Administration-approved Covalent...mentioning
confidence: 99%
“…Fosfomycin is the unique clinically available inhibitor of MurA acting competitively against phosphoenolpyruvate. Its mode of action is related to the covalent binding to the thiol group of Cys115 residue in the active site of MurA ( Kahan et al, 1974 ; Falagas et al, 2016 ; Sutanto et al, 2020 ; Scarpino et al, 2021 ). Naturally produced by Streptomyces spp.…”
Section: Fosfomycin As Food and Drug Administration-approved Covalent...mentioning
confidence: 99%
“…[52][53][54] Flanagan et al found that calculated reaction barrier heights correlate strongly with GSH reactivity (r 2 = 0.92). [55] Calculated reaction barriers coupled with the docking software AutoDock4 led to development of a virtual screening tool, WIDOCK, to support identification of novel covalent inhibitors; [56] performance of the tool was illustrated on several industrially relevant examples (KRAS, MurA, cathepsin B).…”
Section: Prediction Of Covalent Reactivitymentioning
confidence: 99%
“…In vivo chemical reactivity [43] Modeling covalent modification of biological thiols Quantum mechanical/molecular mechanical dynamics simulations (Hirshfeld charges) [44] Predicting covalent warhead reactivity Quantum mechanical modeling of adduct formation [47] Estimating covalent reactivity of acrylamides Quantum mechanical calculations of electrophilicity index [48] Predicting activation energy of acrylamides, 2-chloroacetamides and propargylamides Quantum mechanical calculations of electrophilicity index [49] Assessing organic chemical reactivity Quantum mechanical calculations of Fukui electrophilicity index [51] Predicting the reactivity of covalent inhibitors Quantum mechanical calculations (proton affinity) [52] Automated transition state search Quantum mechanical/molecular mechanical calculations [53] Automated transition state search Quantum mechanical calculations [54] Automated transition state search Quantum mechanical calculations [55] Predicting electrophilic reactivity of covalent inhibitors Quantum mechanical calculations (kinetic reaction barriers) [56] WIDOCK: identifying novel covalent inhibitors Virtual screening, docking [57] BIreactive: estimate covalent warhead reactivity Quantum mechanical calculations, regressor machine learning model predictions. [83,84] The specific conditions necessary for reactions to be amenable for DEL synthesis could be a limiting factor for widespread application of ML reactivity prediction models beyond DELs.…”
Section: Multihead Attention Modelmentioning
confidence: 99%
“…For example, CovDock [20,21] is a workflow utilizing the Glide docking protocol [22][23][24] and Prime protein structure refinement [25,26]; DOCKovalent is a variation of DOCK [27]. AutoDock [28] natively supports covalent inhibitor docking, as do Cova-lentDock [29] and WIDOCK [30], which are based on AutoDock.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports of using covalent docking successfully in the virtual screening and lead optimalization [27,[30][31][32]. However, to our knowledge, none of these covalent docking methods has the capability to deal with flexible receptors.…”
Section: Introductionmentioning
confidence: 99%